Production of recombinant IgA1 with defined mucin-type O-glycans in Nicotiana tabacum BY-2 cells - Bailly, Nicolas; Grünwald-Gruber, Clemens; Peeters, Marie; Chaumont, François; Navarre, Catherine (Frontiers in Plant Science, 2025)
Nicotiana tabacum BY-2 cell suspension cultures are a powerful platform for producing recombinant glycoproteins such as immunoglobulins. Extensive efforts have been devoted to engineering the N-glycosylation pathway of BY-2 cells to overcome differences between mammalian and plant N-glycans. However, the mucin-type O-glycosylation pathway is absent in plant cells. This modification, which consists of glycan attachment to serine or threonine residues, is important in many human proteins, but is also highly complex. In this regard, plants offer a unique opportunity to engineer this pathway de novo without the interplay of many competing enzymes. In this study, transgenic BY-2 cell lines expressing the enzymes responsible for the formation of Core 1 and Tn antigen glycans were generated. First, GalNAc-O-glycosylation was initiated by the expression of human GalNAcT2. This O-glycan was then elongated by co-expression of Drosophila C1GalT1 to form the core 1 structure. Human IgA1 was produced in these engineered BY-2 cell lines and the presence of mucin-type O-glycans was confirmed by lectin blotting. The precise O-glycosylation profile of the hinge region was determined by mass spectrometry and showed the almost complete disappearance of pentoses and the presence of core 1 O-glycans.